IN VITRO ANTIBACTERIAL ACTIVITY AND PHYTOCHEMICAL ANALYSIS OF SOME TRADITIONAL HERBS - RACHNA GARG,; DEVIHALLI CHIKKAIAH MOHANA,; KIRAGANDUR MANJUNATH, (International Journal of Pharma and Bio Sciences, 2013)
Fourteen medicinal plants known as traditional herbs were investigated for in vitro antibacterial activity against Gram-positive Enterococcus faecalis and Staphylococcus aureus and Gram-negative Salmonella typhimurium, Klebsiella pneumoniae and Escherichia coli bacteria using disc diffusion method. The results of screening are encouraging as out of 14 plants, 11 plant extracts (Activity Profile 78.57%) showed antibacterial activity against one or more tested bacterial species. Eight extracts (Activity Profile 57%) inhibited the growth of S. aureus. E. faecalis was the most susceptible bacteria inhibited by 11 plant extracts (Activity Profile 78.57%). Among screened plants only two species (Activity Profile 14%) i.e., Cassia spectabilis and Lantana camara were found active against E. faecalis, S. aureus and K. pneumoniae and between these two species C. spectabilis was found more effective antibacterial agent than L. camara. Phytochemical analysis revealed presence of various phytoconstituents and thus validating their uses in various herbal remedies.